Histoire(s) et traditions éducatives dans l’enseignement-apprentissage du FLE en Hongrie : représentations en tension - Mathieu Houdayer (Recherches en didactique des langues et des cultures)
Over the past seventy years, Hungary has experienced many historical upheavals. As part of the Soviet Union from the end of the Second World War until the fall of the Berlin Wall, this Central European country has had to redesign its organisation at all levels including education. This article starts from the observation that the educational traditions inherited from the teaching of foreign languages in Hungary during the Soviet era still seem to be a point of reference for different generations of teachers of French in different ways. It will be underlined, among other things, that the current educational reforms introduced by an increasingly authoritarian regime have contributed to the re-statisation and recentralisation of the education system and therefore of the textbooks chosen, which gives rise to various reactions among secondary school teachers, partly linked to their life histories and particularly to their professional life. I will focus more specifically on the representations of textbooks through the interpretation of a corpus of comprehensive interviews. The latter were conducted with teachers of French and textbook designers of Hungarian origin working in secondary education and belonging to different generations. In particular, the aim of this study is to understand their representations in relation to their life histories, the traditions they inherit as well as Hungary’s historical developments. It will be highlighted that the representations concerning textbooks are essentially related to political issues, which relativises the weight of primarily methodological aspects in the characterisation of teaching.